Construction interdisciplinaire d’une trajectoire socio-écologique de vulnérabilité à l’exemple du territoire des Quatre Montagnes (Isère, France) de 1950 à 2016 - Thomas Spiegelberger; Agnès Bergeret; Émilie Crouzat; Leita Tschanz; Delphine Piazza-Morel; Jean-Jacques Brun; Dominique Baud; Sandra Lavorel (Revue de Géographie Alpine)
The study of socio-ecosystems, their vulnerability, resilience and their trajectories often involves the need for collaboration between the human and social sciences and the natural sciences. This article proposes to test this notion of "socio-ecosystem" and a methodology around the “chronosystemic timeline" as intermediate tools of interdisciplinary knowledge. It reports on an interdisciplinary experience, its research context as well as its conceptual and methodological framework, illustrated with an example coming from the Quatre-Montagnes in the Vercors (French Alps). It proposes an applicable protocol for monitoring the vulnerability trajectories of a collective of municipalities and its environmental resources in an interdisciplinary perspective. The process consists of four stages : i) a socio-historical and ecological exploratory step ii) the determination of the dimensions to be observed and their indicators, iii) the construction of the timeline, and iv) the analysis of the vulnerability trajectory of a landscape including its actors. The article shows the potential, the methodological difficulties and the points of vigilance of this interdisciplinary analysis.